Relevansi Mathla’ul Anwar terhadap Pendidikan Politik Masyarakat Pandeglang - Ali Nurdin (Perkara : Jurnal Ilmu Hukum dan Politik, 2023)
People’s understansing of political dynamics is very diverse and not focused on one view. This relates to the different an each individual’s understanding of contestation and developing political issues. This study I’m to find the relevance between the Islamic organization Mathla’ul Anwar to the political education of the Pandeglang community. This research uses a field survey research method. The research population or sample was taken from several community groups using interview data collection techniques and instruments, and data analysis tools using data reduction and interpretation. The research results show that there is a lack of relevance of the political education provided by Mathla'ul Anwar to the community because it is not the focus of Mathla'ul Anwar. Mathla'ul Anwar provides political freedom and does not patronize any political power, Mathla'ul Anwar focuses on educational and religious issues, and political decisions are personal decisions.